دراسة عملية لحساب الموصلية الحرارية لنشارة الخشب - كامل داود, هيثم (Journal of Engineering and Sustainable Development, 2010)
The thermal performance of saw dust was studied experimentally to investigate its validity of usage as thermal insulator. The sawdust has low thermal conductivity and cheap in price since it is carpentry waste material. The thermal conductivity is a function of temperature differences, between specimen sides, and its increases as the temperature difference increases. The results showed that the insulation value increases as the density of the samples decreases; this is due to the increase of the volume of air voids and hence increasing of thermal insulation material because of low thermal conductivity of air which resist the flow of the heat through the void. The effect of binders was studied and it showed that the thermal conductivity increases as the binding material increases for the same density, the lowest value of thermal conductivity was 0.18W/moC at lowest density 100kg/m3 without using binder and the highest value of thermal conductivity was 0.285W/moC at highest value of density 250kg/m3 with 40% of binding material.